2018
DOI: 10.1016/j.jsat.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Employment after beginning treatment for substance use disorders: The impact of race/ethnicity and client community of residence

Abstract: Employment is an important substance use treatment outcome, frequently used to assess individual progress during and after treatment. This study examined whether racial/ethnic disparities exist in employment after beginning treatment. It also examined the extent to which characteristics of clients' communities account for such disparities. Analyses are based on data that linked individual treatment information from Washington State's Behavioral Health Administration with employment data from the state's Employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The decline in initiation and engagement in treatment for commercial plans and a lack of improvement for Medicaid plans is concerning, given the availability of effective treatment for substance use disorders and the growing evidence that initiation and engagement in treatment are associated with lower mortality (3)(4)(5)(6)(7)(8). It is also concerning that the narrowing of the gap in performance in initiation and engagement rates between low-and high-performing plans was mostly due to a decline in performance among highperforming plans, which suggests that even high-performing plans struggled to improve substance use disorder treatment rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in initiation and engagement in treatment for commercial plans and a lack of improvement for Medicaid plans is concerning, given the availability of effective treatment for substance use disorders and the growing evidence that initiation and engagement in treatment are associated with lower mortality (3)(4)(5)(6)(7)(8). It is also concerning that the narrowing of the gap in performance in initiation and engagement rates between low-and high-performing plans was mostly due to a decline in performance among highperforming plans, which suggests that even high-performing plans struggled to improve substance use disorder treatment rates.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation and engagement have been endorsed by the National Quality Forum as reliable and valid quality measures. Research has shown that initiation and engagement in substance use disorder treatment is associated with lower criminal justice involvement, unemployment, and mortality (3)(4)(5)(6)(7)(8).…”
Section: Highlightsmentioning
confidence: 99%
“…Living in communities with a higher proportion of Black residents has also been associated with lower likelihood of receiving timely services in the early stages of treatment (Acevedo et al, 2018b), which has been associated with worse criminal justice outcomes . Communities with a higher proportion of Black residents are also associated with a lower likelihood of employment after beginning SUD treatment (Acevedo et al, 2018a), and unemployment might lead to more substance use and/or criminal justice involvement. Segregated neighborhoods also tend to have a higher concentration of alcohol outlets (LaVe ist & Wallace Jr., 2000) and fewer employment opportunities (VonLockette, 2010;Weinberg, 2000), both of which may increase the likelihood of relapse.…”
Section: Discussionmentioning
confidence: 99%